Behavioral experience induces zif268 expression in mature granule cells but suppresses its expression in immature granule cells - Huckleberry, Kylie A.; Kane, Gary A.; Mathis, Rita J.; Cook, Sarah G.; Clutton, Jonathan E.; Drew, Michael R. (Frontiers in Systems Neuroscience, 2015)
Thousands of neurons are born each day in the dentate gyrus (DG), but many of these cells die before reaching maturity. Both death and survival of adult-born neurons are regulated by neuronal activity in DG. The immediate-early gene (IEG) zif268 is an important mediator of these effects, as its expression is induced by neural activity and knockout of zif268 impairs survival of adult-born neurons (Veyrac et al., 2013). Despite the apparent importance of zif268 for adult neurogenesis, its behavior-induced expression has not been fully characterized in adult-born neurons. Here we characterize behavior-evoked expression of zif268 in mature and newborn dentate granule cells (DGCs). In the general granule cell population, zif268 expression peaked 1 hour after novel environment exposure and returned to baseline by 8 hours post-exposure. However, in the doublecortin-positive (DCX+) immature neurons, zif268 expression was suppressed relative to home cage for at least 8 hours post-exposure. We next determined that exposure to water maze training, an enriched environment, or a novel environment caused approximately equal suppression of zif268 expression in DCX+ cells and approximately equal activation of zif268 in the general DGC population and in 6-week-old adult-born neurons. Finally, we asked whether zif268 suppression varied as a function of age within the DCX+ population, which ranges in age from 0 to approximately 4 weeks. Novel environment exposure had no significant effect on zif268 expression in 2- or 4-week-old BrdU-labeled neurons, but it significantly suppressed zif268 expression in 3-week-old neurons. In summary, behavioral experience transiently activated expression of zif268 in mature DGCs but caused a more long-lasting suppression of zif268 expression in immature, adult-born DGCs. We hypothesize that zif268 suppression inhibits memory-related synaptic plasticity in immature DGCs or mediates learning-induced apoptosis of immature adult-born neurons.